2003
DOI: 10.1029/2002gl016422
|View full text |Cite
|
Sign up to set email alerts
|

Molecular synthesis in hypervelocity impact plasmas on the primitive Earth and in interstellar clouds

Abstract: [1] When impact speeds exceed a critical range of $15-20 km s À1 , the resulting plasma plume energizes very rapidly from a few eV, to as high as 30-50 eV when speeds reach 50-100 km s À1, and can be completely atomized and ionized. During post-impact adiabatic dispersion, the degree of ionization drops. The remaining ion population is mostly atomic, sampling the elemental composition of the colliding bodies, but some molecular ions are also formed. We present here results of experiments in which the physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…The high-velocity (10-100 km s K1 ) impact of asteroids or comets, which initially contain prebiotic materials or building blocks of biomolecules, can result in the synthesis of amino acid oligomers (Bernstein 2006). It was experimentally demonstrated that hypervelocity impacts can oligomerize amino acid monomers (Blank et al 2001) and other large organic molecules (Miruma 1995;Managadze et al 2003). Furthermore, organic compounds can also survive such hypervelocity impacts (Pierazzo & Chyba 1999), providing favourable conditions for the exogeneous delivery of organic materials on Earth.…”
Section: The Chemical Universementioning
confidence: 99%
See 2 more Smart Citations
“…The high-velocity (10-100 km s K1 ) impact of asteroids or comets, which initially contain prebiotic materials or building blocks of biomolecules, can result in the synthesis of amino acid oligomers (Bernstein 2006). It was experimentally demonstrated that hypervelocity impacts can oligomerize amino acid monomers (Blank et al 2001) and other large organic molecules (Miruma 1995;Managadze et al 2003). Furthermore, organic compounds can also survive such hypervelocity impacts (Pierazzo & Chyba 1999), providing favourable conditions for the exogeneous delivery of organic materials on Earth.…”
Section: The Chemical Universementioning
confidence: 99%
“…However, there is a distinct possibility that, in other molecular clusters, an impact-induced extreme compression will produce a metallic phase. In such transient metallic clusters, plasma produced by the high-temperature impact may be operative in relevant molecular syntheses (Managadze et al 2003).…”
Section: Impact Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of experiments have shown organic synthesis during shock experiments (e.g., McKay and Borucki, 1997) or during hypervelocity impact-generated plasmas (Managadze et al, 2003a(Managadze et al, , 2003b. It is also possible to fire laser pulses into samples to induce shock effects, and Nna-Mvondo et al (2008) did this with ice targets doped with various materials.…”
Section: Introductionmentioning
confidence: 99%
“…In both experiments and thermodynamic calculations, we consider reaction systems consisting of silica (SiO 2 ) and polyethylene (PE). First, we conduct LPV experiments, which have been used to simulate impact vaporization (e.g., Mukhin et al, 1989;Kadono et al, 2002;Managadze et al, 2003;Sugita et al, 2003;Ohno et al, 2004) and measure whether CO and/or CO 2 are produced in even carbon-poor reaction systems. We use artificial samples, mixtures of silica powder and polyethylene powder, for investigating the effect of silica-derived oxygen.…”
Section: Introductionmentioning
confidence: 99%